Assessment of Environmental Noise in Cities: A Theoretical Approach - Daniel IsaÃ GONZÃLEZ GÃ“MEZ; Rebeca DE HARO MOTA; Susana MARCELEÃ‘O FLORES (Prizren Social Science Journal, 2020)
Environmental noise is a major problem with increasing presence in cities; its effects are not only assimilated into the environment, but also impact on human health. Noise sources are part of the city's daily life and it has not yet been given due attention, although prolonged exposure causes often irreversible physiological and psychosomatic damage.